2002
DOI: 10.1021/ol0261581
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Cyclization of o-Acetoxy- and o-Benzyloxyalkynylpyridines:  An Easy Entry into 2,3-Disubstituted Furopyridines

Abstract: [reaction: see text] 2,3-Disubstituted furo[3,2-b]pyridines, 2,3-disubstituted furo[2,3-b]pyridines, and 2,3-disubstituted furo[2,3-c]pyridines are readily prepared under mild conditions via the palladium-catalyzed cross-coupling of 1-alkynes with o-iodoacetoxy- or o-iodobenzyloxypyridines, followed by electrophilic cyclization by I(2) or by PdCl(2) under a balloon of carbon monoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(80 citation statements)
references
References 25 publications
1
79
0
Order By: Relevance
“…In another paper, Cacchi has demonstrated an analogous cyclization of benzylic ethers to generate furopyridines and reported that the ohydroxyalkynylpyridines are not stable and cyclize spontaneously to give furopyridines (eq 1). 23 We have attempted to make this overall approach more attractive synthetically by examining the preparation and cyclization of the corresponding methyl ethers using a variety of commercially available electrophiles. Herein, we wish to report an efficient approach to 2,3-disubstituted benzo [b]furans and furopyridines involving the palladium/copper-catalyzed coupling of various iodoanisoles and an iodomethoxypyridine and terminal alkynes, followed by electrophilic cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…In another paper, Cacchi has demonstrated an analogous cyclization of benzylic ethers to generate furopyridines and reported that the ohydroxyalkynylpyridines are not stable and cyclize spontaneously to give furopyridines (eq 1). 23 We have attempted to make this overall approach more attractive synthetically by examining the preparation and cyclization of the corresponding methyl ethers using a variety of commercially available electrophiles. Herein, we wish to report an efficient approach to 2,3-disubstituted benzo [b]furans and furopyridines involving the palladium/copper-catalyzed coupling of various iodoanisoles and an iodomethoxypyridine and terminal alkynes, followed by electrophilic cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…23 Herein, we report an efficient approach to various highly substituted 2(3H)-furanones by the electrophilic cyclization of 3-alkynoate esters and acids.…”
mentioning
confidence: 99%
“…This reactivity pattern is also observed upon activation of the alkyne with transition metals. [35][36][37] We first selected the conditions reported by Arcadi et al, [16,17] which use solutions of I 2 in alcohols (ethanol, methanol) in the presence of sodium bicarbonate. Using methyl ethers such as 7, the substrates favored by Larock and colleagues, [31] starting materials were recovered.…”
Section: Resultsmentioning
confidence: 99%
“…For a straightforward entry into the collection of arotinoids with a naphthofuran scaffold (a study expanded to benzofuran analogues as well) we used the iodine-induced 5-endo-dig cyclization of o-methoxynaphthyl-(and o-methoxyphenyl)ethynyl benzoates. [16,17] Diverse aryl, alkenyl, and alkynyl substituents were then appended using Suzuki/Sonogashira coupling reactions. Remarkably, all the steps including the final saponification were carried out with short reaction times and high yields using microwave irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation